Prognostic value and immune-infiltration pattern of FOXD3-AS1 in patients with glioma - Chen, Zhenhua; Zhang, Yi; Feng, Sujuan; Yuan, Jiaqi; Shi, Dongliang; Wang, Yong; Li, Yongdong; Dong, Jun (Frontiers in Pharmacology, 2023)
Glioma is the most typical type of adult primary brain tumor due to its most aggressive nature, with poor prognosis. Gliomas arise from glial precursor cells and are considered one of the most difficult brain tumors to treat because of their rapid proliferation and high invasiveness. Gliomas arise from glial precursor cells and are considered one of the most difficult brain tumors to treat because of their rapid proliferation and high invasiveness. FOXD3-AS1 has been reported to be an emerging potential target for tumor prediction and treatment in many studies. However, FOXD3-AS1 has not been reported in glioma patients so far. In this study, we analyzed the expression differences of FOXD3-AS1 differential profiles in TCGA-GBMLGG database among clinical subgroups. Kaplan-Meier survival analysis and log-rank test analysis of OS, DSS and PFI showed that high expression of FOXD3-AS1 was associated with poor prognosis and survival outcome. Cox regression analysis showed that FOXD3-AS1 as a high risk factor of glioma independently affected the prognosis outcome. Glioma patients showed that patients with high expression of FOXD3-AS1 had poor prognosis. More importantly, because the prognosis of glioma is closely related to the molecular mechanism of oxidative stress, we focused on the analysis of the potential mechanism of six closely related oxidative stress co-expressed genes with FOXD3-AS1. This also reflects that FOXD3-AS1 is closely related to tumorigenesis and prognosis, and has potential application value. At the same time, we found that the immune cell infiltration (ICI) of FOXD3-AS1 and the correlation analysis of immune-related signal markers suggested that the immune cell infiltration was significantly different among immune cell subsets, suggesting that FOXD3-AS1 may affect the prognosis by reshaping the immune microenvironment. Overall, in the current study, we analyzed the relationship between FOXD3-AS1 and glioma for the first time and found that FOXD3-AS1 may influence prognosis by modulating GBM and LGG immune microenvironments. In conclusion, FOXD3-AS1 can be used as a promising prognostic indicator for LGG and GBM, and is closely related to immune infiltration and response to oxidative stress, which may contribute to the development of glioma immunotherapy research.